Prevalence of Musculoskeletal Disorders Among University Professors: An Observational Study at UIAHS, Chandigarh University, Punjab, India - Pathikonda, Sugandha; Pathania, Shivangi (Journal of Neonatal Surgery, 2025)
Musculoskeletal disorders (MSDs) are a significant occupational health concern, affecting professionals across various sectors, including academia. University professors, despite the perceived sedentary nature of their roles, are particularly vulnerable to MSDs due to prolonged sitting, repetitive tasks, and poor ergonomic setups. This observational study aims to determine the prevalence and associated factors of MSDs among professors at Chandigarh University, Punjab, India. Using the Nordic Musculoskeletal Questionnaire (NMQ), data were collected from 256 professors aged 25-50 years with at least one year of academic experience. The results reveal a high prevalence of MSDs, with the lower back, neck, and shoulders being the most commonly affected regions. Female professors reported higher rates of MSDs compared to males. The findings underscore the urgent need for ergonomic interventions and preventive strategies to mitigate the physical and mental strain associated with academic work. Addressing these issues could enhance professors' quality of life and professional productivity.